2021
DOI: 10.1016/j.celrep.2021.109934
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-binding protein FXR1 drives cMYC translation by recruiting eIF4F complex to the translation start site

Abstract: SUMMARY Fragile X-related protein-1 (FXR1) gene is highly amplified in patients with ovarian cancer, and this amplification is associated with increased expression of both FXR1 mRNA and protein. FXR1 expression directly associates with the survival and proliferation of cancer cells. Surface sensing of translation (SUnSET) assay demonstrates that FXR1 enhances the overall translation in cancer cells. Reverse-phase protein array (RPPA) reveals that cMYC is the key target of FXR1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 35 publications
(45 reference statements)
2
37
0
Order By: Relevance
“…Chromosomal abnormalities are common phenomena in development and progression of many human cancers including ovarian carcinoma [ 24 ]. Previously, we have demonstrated that several genes including both protein coding and non-coding genes are aberrantly expressed due to copy number gain in ovarian cancer and in breast cancer [ 17 , 24 , 25 , 26 , 27 , 28 ]. Moreover, chromosomal abnormalities in 1q21 such as amplifications, rearrangements, and translocations, have been reported in several hematological malignancies and solid tumors including endometroid ovarian carcinoma [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal abnormalities are common phenomena in development and progression of many human cancers including ovarian carcinoma [ 24 ]. Previously, we have demonstrated that several genes including both protein coding and non-coding genes are aberrantly expressed due to copy number gain in ovarian cancer and in breast cancer [ 17 , 24 , 25 , 26 , 27 , 28 ]. Moreover, chromosomal abnormalities in 1q21 such as amplifications, rearrangements, and translocations, have been reported in several hematological malignancies and solid tumors including endometroid ovarian carcinoma [ 29 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Along with this assay, we also included the description and tips for both image analysis and quantification of proximal binding sites of FXR1 and its target mRNA by counting of dots representing PLA signal by using image J software. Recently, we have published our enhanced PLA procedure to detect interaction between AU-rich elements present within the 3′UTR region of MYC mRNA and FXR1 protein at the single-cell level in ovarian cancer cell lines ( George et al, 2021 ). In principle, this protocol can be extended to implement the detection of the mRNA-protein as well as protein-protein interaction in a variety of cells.…”
Section: Expected Outcomesmentioning
confidence: 99%
“…This approach will identify several potential binding sites within mRNA. It is highly recommended to perform an RNA electrophoretic mobility shift assay (REMSA) to confirm if the identified sequences exhibit binding affinity with a specific RBP ( George et al, 2021 ).…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations